Α‐Tocopherol transfer protein is not required for the discrimination against γ‐tocopherol in vivo but protects it from side‐chain degradation in vitro. Issue 5 (13th January 2014) - Grebenstein, Nadine; Schumacher, Monika; Graeve, Lutz; Frank, Jan
<x xml:space="preserve">Abstract</x> Scope The mechanisms underlying the preferential retention of a single compound (α‐tocopherol (αT)) of the eight vitamin E compounds in the body are incompletely understood. We hypothesized that vitamin E metabolism and not the hepatic α‐tocopherol transfer protein (TTP) is responsible for the discrimination against non‐αT congeners. Methods and results TTP knockout and wild‐type mice (n = 12/group) were fed equimolar concentrations of αT and γ‐tocopherol (γT; 50 mg/kg diet each) alone or together with sesamin (2 g/kg diet) for 6 wk. Inhibition of vitamin E metabolism with sesamin, but not TTP knockout, increased γT tissue concentrations. TTP‐expressing and TTP‐free cells were incubated with equimolar concentrations of αT and γT (25 μmol/L each) with or without sesamin (2 μmol/L). The preferential degradation of γT independently of TTP expression was confirmed and a decrease in the production of the metabolite γ‐carboxyethyl hydroxychromanol (CEHC) with increasing TTP expression revealed. Displacing γT from TTP in these cells by incubation with increasing αT concentrations enhanced the secretion of γ‐CEHC in TTP‐transfected cells, suggesting that TTP might protect γT from β‐oxidation. Conclusions We conclude that vitamin E metabolism and not TTP controls γT concentrations in vivo and observed an interaction of TTP with vitamin E metabolism that results in reduced production of the metabolite γ‐CEHC.